Área de tabernae tardorromanas en Cartagena - Láiz Reverte, Mª Dolores; Ruiz Valderas, Elena (Antigüedad y Cristianismo, 1998)
Here are presented a group of tabernae discovered in the vicinity of the two streets Orcel and D. Gil, which form part of a group of building which are presently being studied. Chronologically they may be dated between the middle of the fourth century and the end of the fifth AD The irnportance of this discovery is that there is so little archeological evidence in Cartagena from the fifth century, although theoretically it corresponds with a period of growth in that city.